THE EFFECTIVENESS OF HEALTH PROMOTION PROGRAMS IN PREVENTING CHRONIC DISEASES: A META-ANALYSIS - Andro Ruben Runtu (Penelitian dan Pengembangan Ilmu, 2024)
Chronic diseases are a major global health challenge with significant economic and social burden. This study aims to identify the types of health promotion programs that are most effective in preventing chronic diseases and evaluate their effectiveness in various population groups. By using a systematic literature review approach based on PRISMA guidelines, this study analyzed 27 peer-reviewed articles published in the last 12 years. Results show that community and technology (e-health)-based programs have high effectiveness, especially when tailored to the characteristics of the target population. These findings provide important recommendations for policy development and implementation of evidence-based health interventions.